Dual rhodium/copper catalysis: synthesis of benzo[b]fluorenes and 2-naphthalenylmethanones via de-diazotized cycloadditions. Issue 80 (16th September 2016) - Wu, Ya-Nan; Xu, Ting; Fu, Rong; Wang, Nan-Nan; Hao, Wen-Juan; Wang, Shu-Liang; Li, Guigen; Tu, Shu-Jiang; Jiang, Bo
Abstract : A novel synergistic rhodium/copper catalysis has been established, enabling de-diazotized cycloadditions toward the selective formation of benzo[ b ]fluorenes and 2-naphthalenylmethanones. Abstract : A novel synergistic rhodium/copper catalysis has been established, enabling de-diazotized cycloadditions of 1, 5-enynes and α-diazocarbonyls toward the selective formation of densely functionalized benzo[ b ]fluorenes and 2-naphthalenylmethanones. α-Aryldiazoesters result in the formation of triple C–C bonds through bimetallic catalysis whereas a range of functionalized naphthalenes with a 1, 5-dicarbonyl unit were accomplished using α-diazocarbonyls without any substituent at the α-position, indicating that substituents at the α-position of the α-diazocarbonyl unit could control the selectivity of the reaction.